Bulk density, organic matter and texture of soil on forest road at Sapulut, Sabah - Jamal, Norsafiq (2019)
Forest road and trail are needed in order to do forest harvesting operation. Construction and usage of forest road causes increase in soil bulk density. High soil bulk density causes increase in soil compaction. It causes adverse effect on plant growth. Therefore, this study is crucial in order to show the degree of damage done by the current conventional harvesting system. It is important so that it can be revised to reduce damage that otherwise it will inflict to the forest soil. In this study, bulk density, content of organic matter and soil texture of operational forest road soil in Sapulut, Sabah were determined and being compared, that is between primary road, secondary road, and skid road. In this study, it was shown that the soil texture of Sapulut operation area was sandy clay loam while bulk density of soil on forest road ranged from 1.25g/cm3 on skid road to 1.94g/cm3 on primary road. Primary road had the highest soil bulk density compared to secondary road and followed by skid road. However, surprisingly, the data analysis showed that there was different bulk density between the middle of the road and the side of the road. It was shown that the middle of the road had lower bulk density compared to the side of the road which the tire track was always on. Other than that, it was also shown that soil organic matter and organic carbon content was significantly lower on the primary road compared to secondary road and skid road. This shows that the primary road is the most severely degraded followed by secondary road and skid road. This study shows how forest harvesting operation can cause adverse effect to the soil.